The Influences of English on Indonesian Register of Culinary: Pengaruh Bahasa Inggris terhadap Register Kuliner Indonesia - Yulianti, Andi Indah; Septiana, Dwiani; R, Hasina Fajrin (Balai Bahasa Provinsi Papua, 2022)
Register used in the culinary field is very interesting to be studied. The terminologies in the culinary field are commonly using foreign terms and have undergone a shift that contributed to an effect on language shift directly and indirectly. Based on the reasons above, the writer is intending to describe the problems that occur in the language registers used by chefs which have an impact on English for specific work fields. Besides, the language used by the chefs is a part of language variety registers that are interesting to study because the variety of language registers in this field is not found in the other events. Register spoken language is restricted to the use of words and phrases used in spoken language. To achieve the objectives, the author applied a sociolinguistic approach and the research method was descriptive qualitative methods. The authors also make observations by watching some cooking shows on Youtube.